PENERAPAN HUKUM TERHADAP PELANGGAR PERDAGANGAN ORANG (Studi Kasus Putusan Nomor: 1451/Pid.Sus/2021/PN.Mdn) - Jannah, Adinda Fathul; Roza, Ahmad Fadhly (Lex Lectio Law Journal, 2022)
AbstractHuman trafficking is a problem that has not been dealt with explicitly by the Indonesian government or international organizations tasked with handling it. Print and electronic media reports show that law enforcement efforts to eradicate human trafficking are still not optimal. Trafficking in persons is against human dignity and violates their rights, especially when it involves women and children. The research methodology used in this study is a normative legal research method through literature study, which involves gathering information and materials from various sources, including mass press clippings on the issue of human trafficking and legislation related to human trafficking as well as other literature and references. Based on Decision No. 1451/PidSus/2021/PN. The MDN that occurred in Medan concerned the criminal case of human trafficking carried out by parents, namely a mother making her own biological child a commercial sex worker to satisfy a masher. For this criminal act the judge imposed a criminal sanction of imprisonment for 4 (four) years and a fine of Rp. 120,000,000. with the provision that if not paid is replaced with imprisonment of 3 (three) months. Therefore, the defendant remains detained and pays court fees of Rp. 5000, (five thousand rupiah). Human trafficking is caused by various difficulties and problems. Lack of knowledge and poverty force people to seek any type of work when the risks are negligible, as well as cultural factors and weak law enforcement when dealing with the business of trafficking.AbstrakPerdagangan manusia menjadi permasalahan yang belum ditangani secara tegas oleh pemerintah Indonesia atau organisasi internasional yang bertugas menanganinya. Laporan media cetak dan elektronik menunjukkan bahwa upaya penegakan hukum untuk memberantas perdagangan manusia masih belum maksimal. Perdagangan manusia bertentangan dengan martabat manusia dan melanggar hak-hak mereka, terutama ketika melibatkan perempuan dan anak-anak. Metodologi penelitian yang digunakan dalam penelitian ini adalah metode penelitian hukum normatif melalui studi literatur, yang melibatkan pengumpulan informasi dan bahan dari berbagai sumber, termasuk kliping pers massa tentang masalah perdagangan manusia dan perundang-undangan yang berkaitan dengan perdagangan manusia serta literatur dan Referensi lainnya. Berdasarkan Putusan No. 1451/PidSus/2021/PN. MDN yang terjadi di Medan menyangkut tentang perkara pidana Perdagangan Manusia (human Trafficking) yang dilakukan oleh orang tua yaitu seorang ibu menjadikan anak kandungnya sendiri sebagai pekerja seks komersil untuk memuaskan lelaki hidung belang. Atas tindakan pidana tersebut hakim menjatuhkan sanksi pidana penjara pidana penjara 4 (empat) tahun dan denda sejumlah Rp. 120.000.000. dengan ketentuan apabila tidak dibayar diganti dengan pidana kurungan 3 (tiga) bulan. Sehingga demikian, terdakwa tetap ditahan dan membayar biaya perkara Rp. 5000, (lima ribu rupiah). Perdagangan manusia disebabkan oleh berbagai kesulitan dan masalah. Kurangnya pengetahuan dan kemiskinan memaksa orang untuk mencari jenis pekerjaan apa pun ketika risikonya dapat diabaikan, serta faktor budaya dan penegakan hukum yang lemah ketika berurusan dengan bisnis perdagangan manusia.